A simple way to introduce an adjustable femtosecond pre-pulse to enhance laser-driven proton acceleration. (November 2019) - Wang, P; Gao, Y; Shou, Y; Pan, Z; Xu, S; Wang, D; Liu, J; Cao, Z; Mei, Z; Kong, D; Geng, Y; Zhao, Y; et al.
Abstract: We demonstrate a simple way to introduce a femtosecond pre-pulse with adjustable intensity and delay without using an additional compressor to enhance laser-driven proton acceleration. Targets with different thicknesses were shoot at normal incidence by varying the pre-pulses. Experimental results show that significant enhancement of the proton energy can be achieved when the intensity of pre-pulse is optimized. Density profile of preplasma was obtained by hydrodynamic simulations. PIC simulations reveal that the preplasma generated by a femtosecond pre-pulse can increase the intensity of main pulse.